2021
DOI: 10.3389/fphys.2021.734215
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanobiology of Endothelial-to-Mesenchymal Transition in Cardiovascular Disease

Abstract: Endothelial cells (ECs) lining the cardiovascular system are subjected to a highly dynamic microenvironment resulting from pulsatile pressure and circulating blood flow. Endothelial cells are remarkably sensitive to these forces, which are transduced to activate signaling pathways to maintain endothelial homeostasis and respond to changes in the environment. Aberrations in these biomechanical stresses, however, can trigger changes in endothelial cell phenotype and function. One process involved in this cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 114 publications
0
26
0
Order By: Relevance
“…Transforming growth factor beta TGFβ, is the most extensively studied mediator causing endothelial cells to undergo EndoMT. In in vitro experiments investigating the impact of inflammation on EndoMT, TGFβ is used alone as stimuli or in combination with tumor necrosis factor-α (TNFα) and interleukin-1β (IL-1β) [46,47]. A few reports have shown that endothelial-to-mesenchymal transition is induced by mechanical forces (activators) such as flow and shear stress, matrix composition and stiffness, stretch and cyclic strain [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transforming growth factor beta TGFβ, is the most extensively studied mediator causing endothelial cells to undergo EndoMT. In in vitro experiments investigating the impact of inflammation on EndoMT, TGFβ is used alone as stimuli or in combination with tumor necrosis factor-α (TNFα) and interleukin-1β (IL-1β) [46,47]. A few reports have shown that endothelial-to-mesenchymal transition is induced by mechanical forces (activators) such as flow and shear stress, matrix composition and stiffness, stretch and cyclic strain [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro experiments investigating the impact of inflammation on EndoMT, TGFβ is used alone as stimuli or in combination with tumor necrosis factor-α (TNFα) and interleukin-1β (IL-1β) [46,47]. A few reports have shown that endothelial-to-mesenchymal transition is induced by mechanical forces (activators) such as flow and shear stress, matrix composition and stiffness, stretch and cyclic strain [47,48]. Accordingly, endothelial cells' responses to EndoMT triggers are heterogeneous and are dependent on different factors for example mechanical activators of EndoMT cause mechanical hallmarks such as endothelial monolayer disruption and invasion into the extracellular matrix [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ischemic or inflammatory tissue microenvironments with elevated ROS levels, the expression of catalase, copper-zinc superoxide dismutase (Cu/ZnSOD), manganese superoxide dismutase (MnSOD) and anti-apoptotic factor Bcl-2 in EPCs was increased, supporting the supposition that ECs are resistant to ROS-induced toxicity, thereby maintaining their viability and functional activity ( 26 ). In addition, recent studies have shown that the endothelial-mesenchymal transition (EndMT) is an important process in vascular endothelial injury and is closely related to plaque stability and endothelial microenvironment homeostasis in coronary atherosclerosis ( 108 ). The EndMT causes ECs to lose their endothelial characteristics and acquire a mesenchymal-like cell (SMC and fibroblast) phenotype ( 109 , 110 ).…”
Section: Epc Recruitment-related Signaling Pathwaysmentioning
confidence: 99%
“…In the normal physiological condition, this cell fate conversion is necessary to properly form the cardiac valves of the developing heart [ 33 ]. However, EndoMT recurs postnatally during the development of various cardiovascular diseases (CVDs), such as atherosclerosis, adult valve diseases, myocardial fibrosis, and pulmonary arterial hypertension (PAH) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In the EndoMT transitional process, endothelial cells progressively lose endothelial-specific markers and gain mesenchymal phenotypes [ 45 ].…”
Section: Introductionmentioning
confidence: 99%